Protective effect of Stevia Rebaudiana leaf extract on hemolytic behaviour of human erythrocyte in hydrogen peroxide-induced oxidative stress / Norhisham Haron ... [et al.] - Haron, Norhisham (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
Stevia rebaudiana, a member of Asteraceae family is rich in stevioside and total phenolic compounds. The aim of the present study was to investigate the protective effect of Stevia rebaudiana leaf extract on human erythrocytes against oxidative damage, in vitro. The protective effect of Stevia rebaudiana leaf extract in erythrocytes was studied in terms of resistance to hemolysis, lipid peroxidation and morphological changes. Stevia rebaudiana leaf extract at different concentrations (100, 200 and 300 μg/mL) was tested in 10 mM hydrogen peroxide (H₂O₂) induced oxidative stress on human erythrocytes. The hemolysis of erythrocytes induced by H₂O₂ was inhibited in a dose-dependent manner. The Stevia rebaudiana leaf extract was found to inhibit erythrocyte's lipid peroxidation caused by H₂O₂. Morphological alterations in erythrocytes induced by H₂O₂ were protected by the leaf extract. In conclusion, the study demonstrated that Stevia rebaudiana leaf extract protected erythrocytes against oxidative damage due to its antioxidant properties.